XXI century artificial intelligence in education: SWOT-analysis (Journal of Educational Sciences, 2024)
In the 21st century there has been a growing interest in artificial intelligence (AI) which is being applied across a wide range of industries, including banking, automotive, mobile phones, medical research, and personnel training. The potential of AI for science, technology, and the economy is immense, promising to enhance efficiency and improve quality of life. However AI also raises ethical and social concerns, such as the threat of job losses, privacy breaches, and discrimination.This article presents a literature review and an empirical study that evaluates students' and educators' perceptions of the potential applications of AI in education. The opportunities, prospects, and risks associated with the use of AI in education were identified through a SWOT analysis which was based on a meta-analysis of educational literature and surveys conducted among university professors and students from institutions such as the Abai Kazakh National Pedagogical University and the Kazakh National University of Arts.The collected data were analyzed using statistical methods, including descriptive statistics. According to our findings the development of ethical guidelines that ensure data security and equal access to education for all students is crucial for the effective implementation of AI in education. These guidelines should address concerns related to privacy, fairness, and inclusivity, ensuring that the benefits of AI are distributed equitably among all stakeholders in the educational system.In conclusion while AI holds great promise for transforming education, it is essential to approach its integration thoughtfully considering the potential risks and challenges. We can harness the power of AI to enhance the quality and accessibility of education for all by establishing robust ethical frameworks and fostering collaboration between educators, researchers and policymakers.Keywords: artificial intelligence, society, opportunities, digital age, future educators.